Biodiversity resources and livelihoods: A case from Lamabagar Village Development Committee, Dolakha District, Nepal - Shrestha, Uttam Sagar (Geographical Journal of Nepal, 2017)
Biodiversity resources are essential to both ecosystem and livelihood function of human population. The present paper discusses the availability of biodiversity resources and its contribution in the livelihood of local people in Lamabagar Village Development Committee, Dolakha district, Nepal. The results show that the livelihood of local people depends on biodiversity resources and people use these resources as fuel wood, timber, fodder and forage for household consumption. In addition, these resources are used as raw materials for local industry such as paper industry and are exported to other market towns to sell and generate income. Bio-diversity resources contribute about 22 per cent of the total household income in the study area. However, the biodiversity resources are at risk due to deforestation mainly for the development for infrastructures such roads and hydropower projects; over exploitation and absence of effective management practices. The Geographical Journal of Nepal Vol. 10: 105-119, 2017